Inspirasi Konstruksi Dakwah bi al-Hal KH. Abdul Ghofur Lamongan Jawa Timur - Mohammad Rofiq (Risda: Jurnal Pemikiran dan Pendidikan Islam, 2024)
This article discusses the application of the bil al-hal da'wah construction by KH. Abdul Ghofur from Lamongan, East Java, which emphasizes the implementation of concrete actions in da'wah. This da'wah construction, meaning "da'wah through action," highlights the importance of consistency between words and deeds in conveying religious messages. As a charismatic scholar, KH. Abdul Ghofur applies this concept through various social and economic programs aimed at improving community welfare. The article outlines six forms of KH. Abdul Ghofur’s bil al-hal da'wah construction: education, environmental and economic empowerment, economic self-sufficiency of pesantren, charity and generosity, alternative and spiritual healing, and involvement in politics. Through a contextual and practical approach, KH. Abdul Ghofur’s bil al-hal da'wah demonstrates relevance and effectiveness in addressing the real needs of society and creating tangible positive impacts.